2022
DOI: 10.1108/sasbe-01-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Driving factors for lean-BIM implementation in Malaysia’s construction industry: qualitative interview-based study

Abstract: PurposeThe synergy of lean construction and building information modelling (BIM) is an important change and transformation driver in the construction industry. It adds value and increases the productivity of construction processes. However, the implementation of lean-BIM in Malaysia is still lacking despite the accelerating BIM adoption rate. This study, therefore, aims to explore factors that potentially drive construction players to adopt lean-BIM for construction projects.Design/methodology/approachExplorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Islam and Aldaihani (2022) further suggested that this approach is suitable in a context when there is an inadequate theory, whereby in this case where there is a lack of studies on the implementation of BIMFM particularly among digital construction professionals in Malaysia. Similar methodology which is qualitative studies through interviews were conducted in BIM studies in the past, by Alreshidi et al (2017) to identify factors for effective BIM governance; Aziz and Zainon (2022) in exploring lean-BIM driving factors in Malaysia; Li et al (2019) interviewed stakeholders in refining critical factors for BIM adoption; and Wang et al (2018)'s studies on FM team involvement in BIM environment. The qualitative interview technique adopted was proven to be reliable as the aim of the past studies were also to obtain in-depth information, whilst getting flexibility to clarify information.…”
Section: Methodsmentioning
confidence: 99%
“…Islam and Aldaihani (2022) further suggested that this approach is suitable in a context when there is an inadequate theory, whereby in this case where there is a lack of studies on the implementation of BIMFM particularly among digital construction professionals in Malaysia. Similar methodology which is qualitative studies through interviews were conducted in BIM studies in the past, by Alreshidi et al (2017) to identify factors for effective BIM governance; Aziz and Zainon (2022) in exploring lean-BIM driving factors in Malaysia; Li et al (2019) interviewed stakeholders in refining critical factors for BIM adoption; and Wang et al (2018)'s studies on FM team involvement in BIM environment. The qualitative interview technique adopted was proven to be reliable as the aim of the past studies were also to obtain in-depth information, whilst getting flexibility to clarify information.…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly, studies demonstrate BIM as an enabler for Lean construction (Peiris et al , 2022). Studies have demonstrated the application of lean construction and advanced digital technologies, particularly BIM, to improve project quality, productivity and performance (Aziz and Zainon, 2022). Technologies such as BIM as an innovative digital technology, point cloud scanning and virtual/augmented reality (VR/AR) installation equipment have a major impact on how construction projects are delivered (Enshassi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Achieving the synthesis between BIM and lean through using BIM technology functionalities in implementing L.C. management strategies contributes to reducing wastes that occur throughout the construction project’s operations and tasks (Aziz and Zainon, 2022; Eldeep et al , 2022). Lean waste factors include design defects, unanticipated design changes while being carried out, time waste, inventory, overproduction, extra processing and unutilized resources (Rossi et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%